ILLUSTRATIVE ACTIVISM: THE IMPACT OF FEMINIST ART ON GENDER EQUALITY MOVEMENTS - Vishwakarma, Nitin; Dave, Dushyant (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The feminist art’s main objective was to foster gender equality movements by critiquing traditional roles, fighting gender oppression, and speaking up for social reform using visual storytelling. This research paper is dedicated to appraising the role of feminist art in gender equality movements, embracing its historical growth, theoretical underpinnings, and effect on public perceptions besides activism. This study examines the transformative power of feminist art in promoting equality and shifting attitudes toward gender through a critical and interdisciplinary analysis of the literature and some of the important artworks of the feminist movements.